Modeling the Spread of Hepatitis B Disease from the SEIR Model in East Java Using RKF 45 - Sakinun Na'malia; Faisol Faisol; Tony Yulianto (Tensor: Pure and Applied Mathematics Journal, 2025)
Hepatitis B is an infectious disease that has a major impact on public health, especially in East Java Province with a high prevalence of cases. This study aims to model the spread of Hepatitis B using the SEIR model (Susceptible, Exposed, Infected, Recovered) and solved numerically with the Runge-Kutta Fehlberg method (RKF45). Simulation results for 10 years showed that the susceptible population decreased from to individuals, while the exposed compartment increased from to . The infected population peaked at around individuals in year 2 and decreased to individuals, while the cured population continued to increase until it reached at the end of the period. The SEIR model with the RKF45 method proved effective in describing the dynamics of the spread of Hepatitis B mathematically and can be utilized as a predictive tool in supporting public health policy.